2021
DOI: 10.3390/molecules26092604
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Phenols, Polysaccharides and Volatile Profiles of Noni (Morinda citrifolia L.) Juice during Fermentation

Abstract: The change in phenols, polysaccharides and volatile profiles of noni juice from laboratory- and factory-scale fermentation was analyzed during a 63-day fermentation process. The phenol and polysaccharide contents and aroma characteristics clearly changed according to fermentation scale and time conditions. The flavonoid content in noni juice gradually increased with fermentation. Seventy-three volatile compounds were identified by solid-phase microextraction coupled with gas chromatography–mass spectrometry (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…However, M. citrifolia L. fruit has a bitter taste and distinctive rancid taste, making it unsuitable for fresh consumption [3]. According to a recent study, the fermentation process becomes partly free from the undesirable smell [36,37]. However, for the development of functional foods, raw material standardization experiments through setting and analysis of marker compound are required [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, M. citrifolia L. fruit has a bitter taste and distinctive rancid taste, making it unsuitable for fresh consumption [3]. According to a recent study, the fermentation process becomes partly free from the undesirable smell [36,37]. However, for the development of functional foods, raw material standardization experiments through setting and analysis of marker compound are required [25].…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, both hexanoic acid (16.173 mg kg −1 ) and octanoic acid (6.104 mg kg −1 ) presented in significant amounts in URP, but no panelists reported the perception of unpleasant rancid smell. In previous studies, the perception of the sharp rancid smell of ripe noni fruit was arbitrarily attributed to the high levels of hexanoic acid and octanoic acid, without taking account of other influential odour‐active compounds through GC‐O and AEDA analyses (Wall et al ., 2018; Lin et al ., 2020; Wang et al ., 2021). Hence, the significant roles of methyl hexanoate and methyl octanoate in the overall smell of noni fruit were overlooked in their studies.…”
Section: Resultsmentioning
confidence: 99%
“…Some latest studies suggested that fermentation may reduce the rancid smell of ripe noni puree, and Lactobacillus plantarum was found with high efficiency for this purpose (Saelee et al ., 2020; Cheng et al ., 2021; Wang et al ., 2021). Studies also indicated that the unacceptable rancid smell remains noticeable even after long periods of juice fermentation (Almeida et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The changes in the aroma profile of the R–B mixed juice before and after fermentation were detected by a portable electronic nose (PEN 3.5 Portable Electronic nose, Airsense Analytics GmbH, Schwerin, Germany) and analyzed as described by Wang et al [ 21 ] with slight modifications. The electronic nose, an electronic system that imitates the human olfactory system and uses a gas sensor array to identify odor, inhales the aroma profile of the sample to be tested into the instrument and analyzes the composition of the gas components through 10 metal–oxide semiconductor (MOS) sensors (R1, W1C, aromatic; R2, W5S, broad-range; R3, W3C, aromatic; R4, W6S, hydrogen; R5, W5C, arom-aliph; R6, W1S, broad-methane; R7, W1W, sulfur-organic; R8, W2S, broad-alcohol; R9, W2W, sulf-chlor; R10, W3S, methane-aliph) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%